Wpływ odkrywki węgla brunatnego "Koźmin" na pokrywę glebową wsi Kobuzów i Podłużyce = Influence of the brown coal open-pit "Koźmin" on soils of the Kobuzów i Podłużyce villages - Owczarzak, Wojciech; Mocek, Andrzej; Kaczmarek, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper there were analyzed changes in water regime in alluvial soils located in the pra-valley of the River Warta, in Kozubów and Podłużyce villages, in the area under the influence of Koźmin lignite exposure. In this area, the research was conducted twice ? in the 1997 and 2006. Dur-ing a 15-year period, significant changes of ground water lingering were observed, which led to changes in the types of water regime of these soils. A few factors, which have occurred with varying intensity since the 60s, had an impact on the current state of alluvial soils? dir-water relation.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); gleby aluwialne; odwodnienie; gospodarka wodna gleb; alluvial soils; drainage; soil water regime